1997
DOI: 10.1007/s002560050257
|View full text |Cite
|
Sign up to set email alerts
|

MRI gadolinium enhancement of bone marrow: age-related changes in normals and in diffuse neoplastic infiltration

Abstract: Contrast material enhancement in healthy persons can vary greatly (range 3-59%, mean 21%, SD 11%). With increasing age there is a significant decrease in contrast enhancement (Pearson's correlation, P < 0.01). The percentage SI increase in patients with intermediate-grade (biopsy 20-50 vol%) and high-grade (biopsy > 50 vol%) diffuse malignant bone marrow infiltration was significantly higher than in normals (mean 67%, SD 34%, P < 0.001). Low-grade (biopsy < 20 vol%) diffuse malignant bone marrow infiltration c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
73
0
7

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(81 citation statements)
references
References 17 publications
1
73
0
7
Order By: Relevance
“…21 Circumscribed lesions within the bone marrow with low signal intensity in T1-weighted and high signal intensity in T2-weighted STIR images were rated as focal lesions. 22 Lesions larger than 5 mm in longest diameter were measured in three dimensions.…”
Section: Image Analysismentioning
confidence: 99%
“…21 Circumscribed lesions within the bone marrow with low signal intensity in T1-weighted and high signal intensity in T2-weighted STIR images were rated as focal lesions. 22 Lesions larger than 5 mm in longest diameter were measured in three dimensions.…”
Section: Image Analysismentioning
confidence: 99%
“…Major interindividual variations of contrast enhancement in normal individuals (3-59 % increase in SI) have been demonstrated with signifi cantly higher contrast enhancement in younger individuals (Baur et al 1997 ). As a rule of thumb, the authors found an increase >40 % SI, a sign of pathologic bone marrow involvement.…”
Section: Dynamic Contrast-enhanced Imagingmentioning
confidence: 65%
“…11 ). The recolonized red marrow enhances on post-contrast T1w fat-saturated images but in a limited way (<40 %) compared to diffuse neoplastic infi ltration (Baur et al 1997 ;Hillengass et al 2011a ). In a research setting, the lack of ultrasmall-particle superparamagnetic iron ore (USPIO) uptake may indicate a tumor progression or recurrence (Daldrup-Link et al 2009 ).…”
Section: G-csf and Bone Marrow Reconversionmentioning
confidence: 99%
“…Compared to the large number of studies exploring the bone-vascular connect at a cellular level, relatively few clinical imaging studies have been performed. MR perfusion imaging studies have shown that vertebral marrow perfusion is reduced in older subjects [11]. In small animals, appendicular blood flow tends to reduce more in the diaphyses (↓45%) with aging than the metaphyses (↓21-28%) [10] paralleling the marrow conversion from hematopoietic to fatty marrow seen in humans.…”
mentioning
confidence: 99%